Evaluación de la incidencia del carbón vegetal, cal y nutrientes minerales sobre las condiciones físicas del suelo; en una área reforestada con melina (Gmelina arbórea roxb), en el barrio La Victoria, parroquia de Zamora, cantón Zamora, provincia de Zamora Chinchipe - Zambrano Jiménez, Willian Alfonso (2016)
In the project "Management of the fertility of the soils with amendments of charcoal for timber species in the southern Ecuadorian Amazon" executed by the UNL, in the parish and canton Zamora in the 2009-2013 under the auspices of the SENESCYT, whose purpose was to orient to generate alternatives to the reforestation of degraded areas productive, in the framework of a sustained management of the fertility of the soil. In this context ran the present investigation whose objective was to evaluate the incidence of the charcoal, lime and mineral nutrients on the physical conditions of the soil. The studied factors: fertilization: Cal (5 t ha-1), N (200 kg ha-1), P (150 kg ha-1), K (200 kg ha-1), Mg (118 kg ha-1), S (229 kg ha-1), Zn (40 kg ha-1) and without fertilization; and charcoal (0 t ha-1, 3 t ha-1 and 6 t ha-1). The experimental design was bifactorial (2x3), in randomized blocks. The speed of infiltration is determined by the method of double ring. The characteristic curve of moisture was determined with the suction equipment, for which no samples disturbed, were subjected to pressures; 0, 1/10, 1/3 and 15 atm and assessed the physical characteristics of the soil. The speed of infiltration step of the range medium to very fast. All treatments have a low capacity of soil aeration and correspond to physically very poor.